Decreased expression of Sushi Domain Containing 2 correlates to progressive features in patients with hepatocellular carcinoma - Liu, Xin-rui (Cancer Cell Int, 2016)
BACKGROUND: Sushi Domain Containing 2 (SUSD2) has been identified as a regulator of colon and breast cancer. Increasing evidence suggests that SUSD2 plays a key role in tumorigenesis. However, the SUSD2 expression status and its functions in hepatocellular carcinoma (HCC) are still unrevealed. In the present study, we intended to investigate SUSD2 expression status and its correlation with the clinicopathological features in HCC patients. Furthermore,we examined the influence of SUSD2 on the proliferation, apoptosis, invasion and migration of the HCC cell lines HepG2 and SMMC7721. METHODS: We evaluated the SUSD2 expression in HCC tissues and paired normal liver tissues by quantitative real-time PCR and western blotting analysis. The clinicopathological significance of SUSD2 was investigated by immunohistochemistry (IHC) on a HCC tissue microarray. Receiver operating characteristic (ROC) analysis was applied to determine the optimal cut-off score for positive expression of SUSD2. The correlation between SUSD2 protein expression and clinicopathological features of HCC was analyzed by Chi square test. The cell proliferation, apoptosis, invasion and migration potential were observed to detect the functions of SUSD2 in HCC cells. RESULTS: Decreased expression of SUSD2 mRNA and protein were observed in the majority of HCC tissues, compared with paired normal liver tissues. When SUSD2 high expression percentage was determined to be above 52.5 % (area under ROC curve = 0.769, P = 0.000), low expression of SUSD2 was observed in 62.2 % (112/180) of HCC tissues and high expression of SUSD2 was observed in all normal liver tissues (16/16) by IHC. Decreased expression of SUSD2 in patients was correlated with high histological grade (χ(2) = 5.198, P = 0.023), advanced clinical stage (χ(2) = 30.244, P = 0.000), pT status (χ(2) = 33.175, P = 0.000), pN status (χ(2) = 4.785, P = 0.029), pM status (χ(2) = 4.620, P = 0.032). Down-regulation of SUSD2 promoted cell proliferation,invasion and migration,reduced the cell apoptosis. CONCLUSIONS: Our findings suggest that SUSD2 may play as a tumor suppressor in HCC cells and could be served as an additional potential marker for diagnosis.